REASSESSMENT OF THE EARLY–MIDDLE EOCENE PLANKTIC FORAMINIFERAL BIO-MAGNETOCHRONOLOGY: NEW EVIDENCE FROM THE TETHYAN POSSAGNO SECTION (NE ITALY) AND WESTERN NORTH ATLANTIC OCEAN ODP SITE 1051 - LUCIANI, Valeria; Giusberti L. (The Journal of Foraminiferal Research, 2014)
We examined a planktic foraminiferal biostratigraphic record from the Tethyan Possagno section (Venetian Prealps of northeastern Italy) spanning the lower–middle Eocene transition, from Chron C24r to the base of Chron C20r and from Zones E1 to lower E8. Our results provide an updated magnetochronological calibration from the Tethyan realm of the lowest and highest occurrences of the zonal markers. All the foraminiferal biostratigraphic events utilized in the most recent and widely used zonal schemes have been recognized. Most of them are in reasonable agreement with the known magnetochronological calibration, such as the Paleocene/Eocene boundary and lowermost Eocene. However, a number of events, specifically the bases of Morozovella aragonensis, Acarinina cuneicamerata, and Guembelitrioides nuttalli, occurs at a significantly lower position at Possagno than in the most recent zonal schemes. A comparable magnetostratigraphic position has been recorded for the first two bioevents in the western North Atlantic Ocean ODP Site 1051 (Blake Nose, Atlantic Ocean). Furthermore, the base of A. cuneicamerata and the top of M. subbotinae have resulted in a reverse order with respect to the previous schemes thus implying the lack of effectiveness for Zone E6. These events compromise part of the existing biostratigraphic scheme now in use. We propose an alternative definition of the Zone E6/E7a boundary by substituting the base of Astrorotalia palmerae for that of A. cuneicamerata This proposal avoids combining E6 and E7a into a single zone. Additionally, we recorded a significantly different magnetostratigraphic position for the base of Turborotalia frontosa, a critical event for the Ypresian-Lutetian boundary placement. Our biostratigraphic dataset is unique in the integration of deep-benthic foraminiferal events with magnetostratigraphy and calcareous plankton data. Because biostratigraphic data of planktic foraminifera from the Possagno section derive from the same sample set analyzed for calcareous nannofossils, we were ...